PENERAPAN STRATEGI PEMBELAJARAN AKTIF QUICK ON THE DRAW UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN LARUTAN ASAM BASA DI KELAS XI IPA SMA NEGERI 1 KANDIS - Marta Malindo Malindo; Erviyenni '; Rini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to increase student achievement on the subject of Acid-Bases Solution in class XI IPA SMA Negeri 1 Kandis. Form of research is experiment research with pretest-posttest design. The sample consisted of two classes, XI IPA1 as an experiment class and XI IPA2 as a control class randomly selected after tests of normality and homogeneity. Experiment class was given to applied strategy active learning quick on the draw, the control class was not applied strategy active learning quick on the draw. Data analysis technique is used t-test. Based on the results of final processing data use t-test formula obtained  tcount>ttable is  2,24 >1,67, it means that the applying of applied strategy active learning quick on the draw can improve student achievement on the subject of acid bases solution in class XI IPA SMA Negeri 1 Kandis. The calculation of effect size resulted on student achievement was 7,93%.  Keywords: Quick On The Draw, Student achievement, Acid-Bases solution